Implants of Encapsulated Human CNTF-Producing Fibroblasts Prevent Behavioral Deficits and Striatal Degeneration in a Rodent Model of Huntington’s Disease - Emerich, Dwaine F. (J Neurosci, 1996)
Delivery of neurotrophic molecules to the CNS has gained considerable attention as a potential treatment strategy for neurological disorders. In the present study, a DHFR-based expression vector containing the human ciliary neurotrophic factor (hCNTF) was transfected into a baby hamster kidney fibroblast cell line (BHK). Using a polymeric device, encapsulated BHK-control cells and those secreting hCNTF (BHK-hCNTF) were transplanted unilaterally into the rat lateral ventricle. Twelve days later, the same animals received unilateral injections of quinolinic acid (QA; 225 nmol) into the ipsilateral striatum. After surgery, animals were behaviorally tested for apomorphine-induced rotation behavior and for skilled forelimb function using the staircase test. Rats receiving BHK-hCNTF cells rotated significantly less than animals receiving BHK-control cells. No behavioral effects of hCNTF were observed on the staircase test. Nissl-stained sections demonstrated that BHK-hCNTF cells significantly reduced the extent of striatal damage produced by QA. Quantitative analysis of striatal neurons further demonstrated that both choline acetyltransferase- and GAD-immunoreactive neurons were protected by BHK-hCNTF implants. In contrast, a similar loss of NADPH-diaphorase-positive cells was observed in the striatum of both implant groups. Analysis of retrieved capsules revealed numerous viable and mitotically active BHK cells that continued to secrete hCNTF. These results support the concepts that implants of polymer-encapsulated hCNTF-releasing cells can be used to protect striatal neurons from excitotoxic damage and that this strategy may ultimately prove relevant for the treatment of Huntington’s disease.